A Comprehensive Investigation into First-Year University Student Adjustment - Nur'aini, Nur'aini; Miswanto, Miswanto; Munir, Abdul; Pristanti, Nindya Ayu; Ravsamjani, Faridz (Bulletin of Counseling and Psychotherapy, 2024)
The transition from high school to university represents a significant period of change in the lives of first-year students. This adjustment often involves challenges in academic, social, and personal domains, with students needing to adapt to new learning environments, peer dynamics, and, in some cases, independence from family. The aim of this research is to examine differences in first year students' adjustment based on gender, culture, and domicile and living with parents or in a boarding house. The methodology employed in this study utilizes a descriptive comparative approach, which involves the integration of Two Way ANOVA with the Rasch Ranking Model. This integration is achieved by converting the raw data into logarithmic data. The study obtained politomy data using a self-adjustment scale instrument, which was disseminated online. The data were analyzed using the Rasch model. The findings show there are significant differences between the adjustment of male and female students, as well as between the Batak tribe and other tribes. Adjustment is influenced by interactions between gender and ethnicity, as well as between ethnicity and place of residence. However, no major differences in adjustment were observed with respect to specific residences or housing types.